Summer of the monkeys - Rawls, Wilson (New York : Bantam Doubleday Dell Books for Young Readers, 1999)
In the late 1800's, a fourteen-year-old Ozark mountain boy spends the summer trying to recapture monkeys escaped from a traveling circus.
"A Yearling book.".
Booklist.
Elem. School Library Collection.
Wilson's Junior High School.
5.9
Young Adult
Keywords: Monkeys -- Fiction; Monkeys -- Fiction; Oklahoma -- Fiction; Oklahoma -- Fiction